2016
DOI: 10.1016/j.molcel.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

EPOP Functionally Links Elongin and Polycomb in Pluripotent Stem Cells

Abstract: The cellular plasticity of pluripotent stem cells is thought to be sustained by genomic regions that display both active and repressive chromatin properties. These regions exhibit low levels of gene expression, yet the mechanisms controlling these levels remain unknown. Here, we describe Elongin BC as a binding factor at the promoters of bivalent sites. Biochemical and genome-wide analyses show that Elongin BC is associated with Polycomb Repressive Complex 2 (PRC2) in pluripotent stem cells. Elongin BC is recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(159 citation statements)
references
References 56 publications
7
151
0
Order By: Relevance
“…A recent study (Beringer et al, 2016) showed that EloB and EloC indirectly bind to PRC2 by associating with the BC-box containing, PRC2-auxillary factor EPOP (Liefke and Shi, 2015; Liefke et al, 2016). However, EloA was not found to be part of this complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (Beringer et al, 2016) showed that EloB and EloC indirectly bind to PRC2 by associating with the BC-box containing, PRC2-auxillary factor EPOP (Liefke and Shi, 2015; Liefke et al, 2016). However, EloA was not found to be part of this complex.…”
Section: Discussionmentioning
confidence: 99%
“…The complex is also part of a ubiquitin ligase complex along with Cullin5 and Rbx2 that drives degradation of stalled Pol II (Wilson et al, 2013). Two of the subunits of the Elongin complex have recently been linked to PRC2 via their interaction with the newly identified PRC2 interacting protein EPOP (Beringer et al, 2016; Liefke et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…We confirmed co-immunoprecipitation of PRC2 subunits with EZHIP using mass spectrometry for protein identification ( Figure 1G). Recent studies have revealed that the core PRC2 subunits associate with mutually exclusive combinations of auxiliary subunits [28][29][30][31] . The PRC2.1 complex includes EPOP and the PCL proteins, while PRC2.2 associates with JARID2 and AEBP2 30,31 .…”
Section: Ezhip Forms a Stable Complex With Prc2 And Lowers H3k27me3 Imentioning
confidence: 99%
“…In mESCs the Set2‐H3K36me3 enzyme leads to PRC2 mediated H3K27me1 deposition within highly transcribed genes (a modification coupled to RNA polymerase elongation) . Moreover, the Elongin BC And Polycomb Repressive Complex 2 Associated Protein (EPOP) regulate transcription at both H3K27me3 repressed and H3K4me3 active domains . EPOP knock‐out mESCs do not show any altered self renewal and morphology but carry an impaired distribution of H3K4me3, H2Bub and RNA polymerase II, due to EPOP interaction with the H2B deubiquitinase USP7 and impaired control of repressive PRC2‐Jarid2 complex …”
Section: Nuclear Prcs Reveal Unpredicted Interactors and Functionsmentioning
confidence: 99%